Green synthesis of zinc oxide nanoparticles using Catunaregam spinosa (Thunb.) triveng for biologicals applications - Rabina Baraili; Ishwor Pathak; Sugam Sharma; Manisha Bhusal; Khaga Raj Sharma (PLoS ONE, 2025)
Green synthesis, which creates nanoparticles from natural sources such as microorganisms or plant extracts, is a sustainable alternative to traditional chemical methods since it employs less hazardous chemicals and has fewer negative environmental consequences. In this study, the antioxidant, antibacterial, and toxicological properties of ZnO nanoparticles were investigated by synthesizing them using an aqueous extract of Catunaregam spinosa ( C. spinosa ) leaves. X-ray Powder Diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray Analysis (EDX), Fourier Transform Infrared Spectroscopy (FTIR), and UV-vis spectroscopy were used to confirm the formation and properties of ZnO-NPs. FE-SEM investigation indicated a nearly spherical form, and XRD computed an average crystallite size of 12.39 ± 3.84 nm. The UV-vis spectrum showed a high absorption peak at 366 nm. FTIR indicated the existence of bioactive functional groups, which are important for nanoparticle capping and stability. ZnO-NPs showed antibacterial efficacy against Escherichia coli , Shigella sonnei , Klebsiella pneumoniae , and Staphylococcus aureus at 50 μg/mL. The inhibition zones were 9 mm, 13 mm, 16 mm, and 15 mm, respectively. Klebsiella pneumoniae and Staphylococcus aureus had the same minimum inhibitory concentration (MIC) of 6.25 mg/mL. Nanoparticles also demonstrated significant antioxidant activity in the DPPH experiment. Toxicity evaluation against Artemia salina yielded an LC 50 of 55.20 ± 16.19 μg/mL, indicating dose-dependent effects. Overall, this study found that ZnO-NPs generated with Catunaregam spinosa leaf extract have promising antibacterial, antioxidant, and toxic characteristics, indicating potential biological applications.